Instructional Challenges in Biology Classrooms in Selected Senior High Schools in the Eastern Region, Ghana - Amoah, John Ekow Mbir; Eminah, Cosmos; Korlie, Sophia (European Journal of Applied Sciences, 2025)
This study thoroughly examined the instructional challenges associated with teaching and learning of biology across selected schools in the Eastern Region, Ghana. It also focused on the availability of resources as well as the dominant pedagogical approaches utilized in the teaching and learning of the subject. Data was obtained from 26 biology teachers and 480 students across 16 senior high schools (SHSs) within the region. The study was a descriptive study hinged on a quantitative approach. The main instrument for data gathering was a questionnaire which was also backed with the use of an observation checklist. The Cronbach alpha reliability of the main instrument was measured to be 0.86 which implied it was adequate to be used for data gathering. It was revealed that lack of instructional resources, use of poor teaching approaches and poor attitude of students were major challenges inhibiting the effective teaching and learning of biology at the SHS level within the region. Recommendations for addressing these challenges included the provision of resources and the conduct of professional development sessions for teachers on innovative instructional methods, teacher motivation among others.